INFORMATION AND TECHNICAL STATE OF THE AUTOMATED SYSTEM OF AIR TRAFFIC CONTROL - E. A. Bolelov; K. N. Matuhin; A. V. Sbitnev; S. V. Shalupin (Научный вестник МГТУ ГА)
The article introduces the concept of information technology state of the automated system of air traffic control and defines the types of information and technical conditions.